EMPLOYEE PARTICIPATION IN DECISION MAKING AND ORGANISATIONAL PERFORMANCE At KCCA IN KAMPALA-UGANDA. A CROSS-SECTIONAL STUDY. - Robert Nimwesiga (Student's Journal of Health Research, 2023)
Introduction: The main aim of this study was to investigate the relationship between employee participation in decision-making and the performance of organizations. The objectives of the study were; to examine the influence of consultative participation in decision-making on performance. Methodology: The study adopted both descriptive and correlational survey research designs based on a quantitative method of data. The study population was 132 out of which a sample of 118 respondents was selected as the study sample and it was randomly selected. Questionnaires and interviews were used as data collection methods. Results: The results of the study revealed a strong positive and significant correlation between consultative decision-making and performance (r= 0.651, p=0.000). Conclusion: The  findings of the study indicated that consultations within organizations are the most required strategy of decision-making within public institutions like KCCA in Uganda.   Recommendation: The study recommends that KCCA should focus on improving the working schedules to make them more flexible as this increases the commitment of employees.